Pernikahan Dini dalam Pandangan Masyarakat Palembang (Studi Fenomenologi di Kecamatan Gandus) - Bety Bety (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2017)
Early marriage is still common and is one of the reproductive problems facing the present. This is often caused by economic factors, education, self and parent. This research was conducted in Palembang city precisely in District Gandus. The purpose of this study is to know the views of the Gandus community, religious figures and marriage figures related to marriage at a young age, and to determine the factors causing early marriage and how the implications for the sustainability of married couples early married. By using the method of quantitative, the object of research are those who carry out the marriage of young age which amounted to 60 people. Data obtained through observation, interviews with married couples married young. From the analysis of the appointment of factors causing the high level of early marriage in Gandus District is the low economic and family education and fear parents will have sex before marriage. The perception of Gandus society related to the number of negative impacts rather than positive one cause divorce is married young, the ego of each pair is still high. In the case of early marriage, young couples should prepare them physically and mentally among them to follow religious social activities and understand the purpose of marriage because after marriage will be many problems that will be faced by the couple.